Man-of-War Bay, Tobago, B.W.I. - Sobrian, C. (Art Photo Studio,[Trinidad and Tobago], 2011)
This postcard shows a beautiful view, from a headland, of Man of War Bay a large bay off the north-eastern coast of Tobago and the village of Charlotteville. It encompasses many smaller bays such as Hermitage Bay, Cambleton Bay, Lover's Bay, Waterfall Bay, Dead Man's Bay and Pirate's Bay. The postcard, postmarked 1956, is addressed to Mrs. Hazel Freeman. Postcard number B3280.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Scenic overlooks--Trinidad and Tobago; 1956; Beaches--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Charlotteville